National health data linkage and the agreement between self-reports and medical records for middle-aged and older adults in Taiwan - Ching-Ju Chiu; Hsiang-Min Huang; Tsung-Hsueh Lu; Ying-Wei Wang (BMC, 2018)
Abstract Background Characteristics associated with acceptance of dataset linkages and health data linkage data quality were analyzed. Methods Participants from the 2011 Taiwan Longitudinal Study on Aging were asked to link their epidemiological data with concurrent and future medical claim datasets. Characteristics associated with acceptance of data linkage, data consistency, under-reporting, and over-reporting of disease conditions were identified. Results Among the 3727 respondents, 3601 (96.6%) accepted data linkage. Middle-aged adults with worse functional health accepted data linkage. Older adults (65+) with better health behavior and social support were more likely to accept data linkage. Consistency between self-reports and medical data was very good to satisfactory (Kappa = 0.80 and 0.67, respectively, for diabetes and hypertension). Comorbidities were common risk factors resulting in inconsistency between self-reports and medical data (OR = 1.58 and 1.27, respectively, for diabetes and hypertension). Living alone was another risk factor resulting in inconsistency for diabetes. Male, older, and not living alone were other risk factors resulting in inconsistencies for hypertension. Under-reporting of illness was associated with poor health and older age. Over-reporting of illness was associated with better health and younger age. Discussion The findings suggest different adjustment methods for middle-aged versus older respondents when considering self-report data validity.